Obtaining a Fuzzy Classification Rule System a Non-Supervised Clustering - Hasperué, Waldo
The fuzzy classification systems have been broadly used to solve control decisionmaking problem. However, its design is complex, even when having a human expert assistance.This paper presents a new strategy capable ofautomatically defining the corresponding Fuzzy Classification Rule System a nonsupervised clustering of the available data. Its application to three data sets of the UCI repository has given quite satisfactory results.